Development Entrepreneurship Intention as an Effort to Improve the Level of the Consumer Household Economy - Halizah, Siti Nur; Darmawan, Didit (Bulletin of Science, Technology and Society, 2023)
Poverty and unemployment are two things that are closely related to each other. Macroeconomically, this will have an impact on the level of economic growth of a country. To reduce it, various efforts are needed starting with the provision of jobs so that the unemployment rate decreases and has an impact on increasing income levels. Unemployment efforts can be overcome in two ways, namely providing job opportunities and creating independent businesses. The effectiveness of overcoming unemployment is carried out by creating independent businesses which are realized by the emergence of new entrepreneurs. The existence of entrepreneurship is preceded by entrepreneurial intentions. The application of the concept of entrepreneurship begins with the intention. This paper will review the entrepreneurial intention and the constituent elements and their relationship to the development of consumer households.